Designing Library Applications with the Application of the Web-Based Dewey Decimal Classification Method (Case Study at SMA GIKI 2 Surabaya) - Putra, Sabdo Wicaksono; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
SMA GIKI 2 Surabaya is a senior high school education institution that located at JL. Raya Gubeng No. 45 Surabaya. SMA GIKI 2 Surabaya has facilities to support students' activities in learning. One of them is the Library facility which has 5000 book collections and is categorized into shelves. Currently the library facilities owned by SMA GIKI 2 Surabaya some of its activities are still carried out manually such as the process of finding books by students must search the bookshelves  that  takes time besides the library officers in recording loans, returns, book collection, book classification and report making is still carried out in a conventional way because there is no development automation system in library.Based on these problems, it is good to use information technology that is computerized in the library of SMA GIKI 2 Surabaya. The construction of library application aims to facilitate the needs of students and librarians in searching catalogs in libraries to the maximum, reduce errors, and present data accurately.book classification and report making is still carried out in a conventional way because there is no development automation system in library.